A comparative study of Filipino and Taiwanese students' mathematical communication skills based on Ill-structured tasks - De Vera, Jeffry, P.; Joaquin, Ma. Nympha B.; Ulep, Soledad A.; Monterola, Sheryl Lyn C. (Quezon City College of Education, University of the Philippines Diliman, 2020)
This study analyzed and compared Filipino and Taiwanese students' mathematical communication skills (written, oral, and representational) based on ill-structured tasks. In addition, it analyzed how the curriculum, environment, technology, student learning opportunities, and teacher characteristics are associated with students' mathematical communication skills.

This was a qualitative case study that involved seven grade 10 top performing students in mathematics from Chinese Filipino, Filipino Special Science, and Taiwanese classes. The students' written and representational mathematical communication skills were assessed using Mathematical Communication Test. The students' answers and solutions in the test were numerically scored using the Quantitative Holistic Scoring Guide and were categorized using Qualitative Analytic Scoring Guide. Moreover, the students' oral mathematical communication skills were assessed through a series of interviews and classroom observations and with the use of scoring guide. Data for the curriculum, environment, technology, student learning opportunities, and teacher characteristics were gathered through documents analysis, interviews, audio-visual recordings, and survey questionnaires.

Findings indicate that of the seven students, three had superior, two had above average, and two had average written mathematical communication skills. Additionally, students exhibited different solution strategies, justification soundness, and mathematical understanding. Chinese Filipino students had high while both Taiwanese students and Special Science students had average oral mathematical communication skills. The findings likewise indicate that the students used multi-modal representations. Moreover, the curriculum, technology, environment, student learning opportunities, and teacher characteristics were found to be all associated with students' mathematical communication skills. Major similarities and significant differences were noted in terms of these factors among the three groups of students.

It was concluded that Chinese Filipino, Special Science, Taiwanese students are able to express and convey mathematical ideas accurately in a clear and logical manner. Chinese Filipino students have better written and oral mathematical communication skills than both Taiwanese and Special Science students. Moreover, Chinese Filipino students use more representation modes than both Special Science and Taiwanese students.

It was also concluded that students who receive more and advanced mathematics curriculum may have higher mathematical communication skills. Additionally, the characteristics of the classroom's physical dimension and social dimension play a role in establishing communication-fostering learning environment for students. Furthermore, the more the students spend time and the more they are exposed to using mathematics software and mathematics forums, the more chance that they will have higher mathematical communication skills. Likewise, the more the students spend time and the more they are immersed in a variety of opportunities in learning mathematics, the better their mathematical communication skill become. And finally, teacher's teaching styles and teaching beliefs are specific factors associated with students' mathematical communication skills.
In light of the findings, policy makers should issue a clear set of guidelines on the mathematics topics for Special Science class. Future researchers may investigate the use of ill-structured tasks as an intervention for a quasi-experimental study. Recommendations are likewise given to students, parents, teachers, textbook writers, and curriculum developers.
Thesis
Includes bibliographical references
Keywords: Mathematics -- Study and teaching (Secondary); Mathematical ability -- Study and teaching (Secondary); Mathematical ability -- Evaluation; Communication in education; High school students -- Philippines -- Bayambang (Pangasinan); Filipino Chinese students -- Philippines; High school students -- Taiwan -- Taipei City